European welfare state regimes and their generosity toward the elderly - Axel Börsch-Supan (Levy Economics Institute of Bard College, 2006)
This paper examines the generosity of the European welfare state toward the elderly. It shows how various dimensions of the welfare regimes have changed during the past 10 to 15 years and how this evolution is related to the process of economic integration. Dimensions include general generosity toward the elderly and, more specifically, generosity toward early retirement and generosity toward the poor. Using aggregate data (EUROSTAT, OECD) as well as individual data (SHARE, the new Survey of Health, Ageing, and Retirement in Europe), the paper looks at the statistical correlations among those types of system generosity and actual policy outcomes, such as unemployment and poverty rates among the young and the elderly, and the inequality in wealth, income and consumption. While the paper is largely descriptive, it also tries to explain which economic and political forces drive social expenditures for the elderly in the European Union and whether spending for the elderly crowds out spending for the young.
Keywords: D1; H55; J26; 330; Welfare state; intergenerational redistribution; pension systems